2007
DOI: 10.1177/0886260506295380
|View full text |Cite
|
Sign up to set email alerts
|

Partner Stalking and Implications for Women’s Employment

Abstract: In general research suggests partner violence has a negative impact on women's employment. However, there has been limited examination of partner stalking and consequences for employment. The purpose of this study was to examine partner stalking and employment consequences among two samples of women. One sample was women who had obtained a protective order against a violent partner and had worked in the prior year (n = 482), about one half of these women were stalked by their violent partner and one half were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 37 publications
4
95
0
2
Order By: Relevance
“…Mon 2016 Workplace HealtH & Safety Bell, 2003;Browned, Salomon, & Bassuk, 1999;Crowne et al, 2011;Hayes, 2012;Kimerling, et al, 2009;Lindhorst et al, 2007;Logan et al, 2007;Moe & Bell, 2004;Postmus et al, 2012;Riger et al, 2004;Staggs, Long, Mason, Krishman, & Riger, 2007;Swanberg, Macke, & Logan, 2006;Swanberg et al, 2007;Tolman & Rosen, 2001;Yragui, Mankowski, Perrin, & Glass, 2012). Similarly, this study found employment maintenance equally difficult for women experiencing IPV.…”
Section: Characteristic Exemplarsupporting
confidence: 49%
“…Mon 2016 Workplace HealtH & Safety Bell, 2003;Browned, Salomon, & Bassuk, 1999;Crowne et al, 2011;Hayes, 2012;Kimerling, et al, 2009;Lindhorst et al, 2007;Logan et al, 2007;Moe & Bell, 2004;Postmus et al, 2012;Riger et al, 2004;Staggs, Long, Mason, Krishman, & Riger, 2007;Swanberg, Macke, & Logan, 2006;Swanberg et al, 2007;Tolman & Rosen, 2001;Yragui, Mankowski, Perrin, & Glass, 2012). Similarly, this study found employment maintenance equally difficult for women experiencing IPV.…”
Section: Characteristic Exemplarsupporting
confidence: 49%
“…This study also adds to prior work that has demonstrated the need for workplace training and policies [7,12,13,34] by identifying the stated needs of supervisors and demonstrating that these needs vary across workplaces. In particular, supervisors believe training should include recognition tools for supervisors and coworkers to be able to recognize both physical and emotional abuse.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, internalized beliefs (Sanders, 2013) also limit potential (Renzetti, 2009). As well, an abusive partner's presence at place of employment to intimidate is also a significant threat to safety (Logan, Shannon, Cole & Swanberg, 2007). In addition, housing instability (Pavao, Alvarez, Baumrind, Induni, & Kimerling, 2007) and lack of transportation (Simmons, Farrar, Frazer, & Thompson, 2011) may also contribute to her decision to stay.…”
Section: Financial Issuesmentioning
confidence: 98%